2019
DOI: 10.3390/ijms20123111
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Estrogens on Platelets and Megakaryocytes

Abstract: In women, oral menopausal hormonal therapy (MHT) is associated with adverse effects including an increased incidence of thromboembolic events, classically attributed to an increase in several liver-derived coagulation factors due to hepatic first pass. While platelets are central players in thrombus constitution, their implication in women treated with estrogens remains incompletely characterized. Platelets and their medullar progenitors, megakaryocytes, express estrogen receptors (ER) that may explain, at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 65 publications
1
30
0
2
Order By: Relevance
“…This induction of hypercoagulation indicates an interplay between oestrogen-induced platelet activation as well as activation due to the cytotoxic nature of Tamoxifen itself 15 17 . The precise mechanism by which Tamoxifen exerts its procoagulant effect remains to be discovered 7 , 18 ; however, studies implicate the anti-oestrogenic activity of the drug on oestrogen receptor alpha (ERα), particularly on those expressed by platelets , to further increase the risk of VTE 19 , 20 ; and further effects on Factor VIII in promoting thrombotic events via its role in platelet activation 18 .…”
Section: Introductionmentioning
confidence: 99%
“…This induction of hypercoagulation indicates an interplay between oestrogen-induced platelet activation as well as activation due to the cytotoxic nature of Tamoxifen itself 15 17 . The precise mechanism by which Tamoxifen exerts its procoagulant effect remains to be discovered 7 , 18 ; however, studies implicate the anti-oestrogenic activity of the drug on oestrogen receptor alpha (ERα), particularly on those expressed by platelets , to further increase the risk of VTE 19 , 20 ; and further effects on Factor VIII in promoting thrombotic events via its role in platelet activation 18 .…”
Section: Introductionmentioning
confidence: 99%
“…Many trials done previously have found that platelet function reduces significantly following oestrogen therapy. 25 The proposed reason was that oestrogen increases the prostaglandin level which in turn reduces platelet aggregation and function. However, the exact mechanism of how oestrogen increases prostaglandin level remains unknown.…”
Section: Resultsmentioning
confidence: 99%
“…The gender influence on platelet biology was shown several years ago [26] and recent studies reported a higher number of fibrinogen surface receptors and a greater ability to bind fibrinogen in women [27]. In addition, estrogens have been shown to enhance platelet production [28]. All these data are important since a direct association has been shown between platelet count and major cardiovascular risk factors [29].…”
Section: Discussionmentioning
confidence: 97%